Habitat characteristics and threats of little-known endemic dragonfly, Neurothemis feralis (Burmeister, 1839) (Odonata: Libellulidae) in East Java, Indonesia - MUHAMAD AZMI DWI SUSANTO; ZULFAIDAH PENATA GAMA; AMIN SETYO LEKSONO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Susanto MAD, Gama ZP, Leksono AS. 2024. Habitat characteristics and threats of little-known endemic dragonfly, Neurothemis feralis (Burmeister, 1839) (Odonata: Libellulidae) in East Java, Indonesia. Biodiversitas 25: 2907-2920. Neurothemis feralis is a dragonfly with limited distribution and is found only in the lowlands of Java, Sumatra, Krakatau, and Bangka. Its habitats that traverse anthropogenic area face various threats from human activities. Despite the imminent of its depopulation, many essential information regarding the biology of N. feralis remain scarce, deem it with data deficient conservation status according to the International Union for Conservation of Nature (IUCN) Red List. This study aims to study habitat characteristics of N. feralis for future conservation purposes. This study was conducted in Surabaya, Sidoarjo, and Gresik, East Java Province, with a five-month study period of July-November 2023. The results showed that N. feralis prefers locations with 36-64% air humidity, 29.2-35.8°C air temperature, and 16970-36400 lux light intensity. Air humidity positively correlated with the abundance of N. feralis, while high temperatures and light intensity tend to have negative impact. The coverage of vegetation with 20-100 cm height was found as another habitat component that positively affects its abundance, while the loss of this coverage understandably negate the dragonfly abundance. Vegetation provides habitat for N. feralis, as well as its prey, competitors and even predators. Despite N. feralis population can still be observed from urban areas with up to 82.40% residential allotment (within 500 m radius of the study site), the disappearance of its population is likely if believably impending if anthropogenic activities (e.g., land conversion and vegetation burning) continue to occur.